Distance Learning during the 2020 COVID-19 Lockdown: The Experience of Italian Middle School Students - Lynda S. Lattke; Aurelia De Lorenzo; Beatrice Tesauri; Emanuela Rabaglietti (MDPI AG, 2022)
Northern Italy was one of the first European regions to be affected by COVID-19 restrictions which led to school closures and the compulsion to learn from home. This article examines middle school students' experiences with distance learning to determine what they found most difficult, what they liked most and what they liked least during the 2020 lockdown. A total of 285 students (56% female; 44% male) with mean age of 13 years (±1 year; min = 11; max = 15) completed the online questionnaire. Responses to three open-ended questions were analyzed and coded using content analysis and an inductive approach. SPSS 26 was then used for descriptive analysis based on the frequencies of the categories that emerged: Learning, Device, Relationship, Other, Environment, Nothing, and Time. The results suggest that important aspects of students' lives during the lockdown had dual meanings. For example, technological devices were experienced as a means of communication, learning, and maintaining relationships, but were also associated with inequities, technical difficulties, and misunderstandings. Student responses support schools' role as a place to foster technological skills, especially social and emotional skills, in order to develop concrete strategies to assist students and teachers improve their relationship skills and be better prepared for future pandemics.